The Influence of Reputation Perception on Customer Behavioral Intentions in Mobile Banking Adoption Based on the Technology Acceptance Model - Iskamto, Dedi; Jenita, Jenita; Nabila, Syadza Muthi; Aftanorhan, Asyraf; Karim, Kurniati (Asosiasi Dosen Peneliti Ilmu Ekonomi dan Bisnis Indonesia (ADPEBI), 2025)
This study aims to describe the mechanism by which perceived reputation influences customers' behavioral intentions related to mobile banking adoption. The study consisted of 385 samples analyzed using a Structural Equation Model (SEM). The results indicate thatPerceived reputation has a positive and significant relationship with trust, perceived ease of use, and behavioral intention. However, it has a positive but insignificant relationship with perceived risk and perceived benefit. Furthermore, trust has a positive and significant relationship with perceived benefit, perceived ease of use, and behavioral intention. However, it has a negative and significant relationship with perceived risk. Furthermore, perceived risk has a positive but insignificant relationship with perceived benefit and perceived ease of use. However, it has a negative and insignificant relationship with behavioral intention. Furthermore, perceived ease of use has a positive and significant relationship with perceived benefit and behavioral intention.Finally, perceived benefits have a positive and significant relationship with behavioral intentions.